Backup Control of Wind Power Generation System Based on Voltage-Sensorless and LCL Active Damping Scheme. Issue 1 (February 2015) - Zhang, Jianwen; Wang, Haisong; Wang, Han; Zhu, Miao; Cai, Xu
Under the fault condition of voltage sensors, the wind power generation system requests an effective backup control scheme without voltage sensors. In order to save sensors for the grid-connected inverter (GCI) with LCL-filter in the full-scale wind power converter, a grid-side voltage-sensorless solution scheme is presented in this paper. A frequency-adaptive SOGI (FA-SOGI) is introduced to realize the virtual flux (VF) estimation. A grid-side voltage observer is thus designed to acquire the phase angle and amplitude, which can realize voltage orientation control (VOC) for the GCI system. With an improved feedback damping method for LCL filter, a full control strategy of the full-scale wind power generation system is given and explained in detail. All theoretical results have been validated by the simulation, followed by analysis and discussion.